2013
DOI: 10.2514/1.c000320
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Spanwise Flow Development on an Insect-Like Rotating Wing

Abstract: This paper presents an experimental investigation of the spanwise flow development on an impulsively started rotating rectangular wing at 45 deg angle of attack. Reynolds numbers of 500 and 15,000 were studied, which correspond to insect and flapping-wing micro-air-vehicle scales, respectively. Stereoscopic particle image velocimetry flowfield measurements were taken at various spanwise locations and sweep angles (angle of rotation from start) on a motor-driven rectangular wing immersed in a seeded water tank.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Note that Carr et al (2013a) showed both positive (outboard) and negative (inboard) spanwise velocity in the vicinity of the LEV for A = 2 and 4, which was also found by e.g. Lu & Shen (2008), Jardin et al (2012), Phillips & Knowles (2013) and Garmann & Visbal (2014). To gain insight into the individual contributions of the positive and negative u axial , we calculate the non-dimensional volume flow rate conditionally on its positive and negative components; this is given in figure 10(a,b) for A = 2 and 4, respectively.…”
Section: Lev Tilt Axial Flow and Vorticity Fluxmentioning
confidence: 57%
See 1 more Smart Citation
“…Note that Carr et al (2013a) showed both positive (outboard) and negative (inboard) spanwise velocity in the vicinity of the LEV for A = 2 and 4, which was also found by e.g. Lu & Shen (2008), Jardin et al (2012), Phillips & Knowles (2013) and Garmann & Visbal (2014). To gain insight into the individual contributions of the positive and negative u axial , we calculate the non-dimensional volume flow rate conditionally on its positive and negative components; this is given in figure 10(a,b) for A = 2 and 4, respectively.…”
Section: Lev Tilt Axial Flow and Vorticity Fluxmentioning
confidence: 57%
“…Granlund et al (2013) showed that the lift and drag coefficients for wing rotation increase at a lower rate and achieve lower final values than for translation, and that C L is generally Re-independent for Re = 14-10 000. Phillips & Knowles (2013) used S-DPIV in select constant-span planes to investigate spanwise velocity for an A = 2.5 rotating rectangular wing at 45 • angle of attack. Similar to Lu & Shen (2008), they measured strong positive and negative velocities, attributing the latter to an effect of the TV velocity and commenting on a likely dependence on wing geometry.…”
Section: Introductionmentioning
confidence: 99%
“…For liquids such as oils and water, seeding particles are normally solid and of similar density to that of the working fluid. Examples include hollow glass spheres of varying sizes (typically tens of microns in diameter) [72,75,89,106]; powders such as polyamide powder [124,[158][159][160] or polymethylmethacrylate powder [111,112,153]; and metallic-coated hollow plastic spheres [27,88,99,167,168]. Occasionally bubbles have been used as seeder particles; however, these can be challenging to work with [59,120,169,170].…”
Section: Rig Implementation Considerationsmentioning
confidence: 99%
“…The Cranfield University research team conducted studies to ascertain spanwise flow at Reynolds numbers of 500 and 15 000 [75,89], figure 9 d . Glass seeding particles were used for the PIV system to take quantitative flow measurements.…”
Section: Experimental Rigsmentioning
confidence: 99%
See 1 more Smart Citation